2016
DOI: 10.15436/2376-0494.16.728
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of Diabetes Prevention by High-amylose Rice and Super Hard Rice

Abstract: Diabetes is one of the most devastating diseases in the world. Its prevention is very important in addition to the development of the curing technology. We started the cooperative research on low Glycemic Index (GI) rice to prevent diabetes. High-amylose rice is promising to prevent diabetes because its GI is lower than low-amylose one. Since Hoku243 presents fewer short-branched glucans and more long chains in the amylopectin starch, its starch is resistant to gelatinization and the boiled rice grains are non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…30 For example, 'super-hard' high-amylose rice could be used for diabetic patients, 31 low-protein or low-gluterin rice for patients with renal failure, 32,33 GABA-rich large germ rice is expected to improve mental health, 34 and rice with high antioxidant properties would be effective for the prevention of cancer and other diseases. 35,36 Human data are accumulating, so we believe it is time to introduce the concept of medical rice for disease prevention and treatment (Table 3).…”
Section: Concept Of Medical Ricementioning
confidence: 99%
“…30 For example, 'super-hard' high-amylose rice could be used for diabetic patients, 31 low-protein or low-gluterin rice for patients with renal failure, 32,33 GABA-rich large germ rice is expected to improve mental health, 34 and rice with high antioxidant properties would be effective for the prevention of cancer and other diseases. 35,36 Human data are accumulating, so we believe it is time to introduce the concept of medical rice for disease prevention and treatment (Table 3).…”
Section: Concept Of Medical Ricementioning
confidence: 99%
“…Physicochemical properties of starches from 13 adzuki bean cultivars revealed significant differences that could be due to variability in granular size, shape, and amylose‐to‐amylopectin ratio. Four out of 13 varieties had 20% high amylose content, making it an appropriate ingredient for diabetic people as high amylose content inhibit increase in blood glucose levels (Kabir et al, ; Liu et al, ; Ohtsubo et al, ). EC‐340255, ICSMLAB‐1, IC‐469173, and EC‐15257 varieties had very low setback viscosity suggesting their possibilities to be used for frozen foods.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the variation in GPR was primarily due to the longer digestion time (GPR=TGP/ADD) in this study. The possible explanation for prolonged digestion time is that the texture of rice noodles was harder than cooked rice, and digestive enzymes could hardly enter the interior for amylolysis 23 . Therefore, our ndings showed that the glucose concentration of the in vitro digested rice noodles reached the maximum value was signi cantly lower than that of cooked rice, which is essential for controlling blood glucose diabetic patients 19 .…”
Section: Discussionmentioning
confidence: 99%